Periurban forests shifting from recreation to wellness - Pascal Papillon; Rodolphe Dodier (Revue de Géographie Alpine)
In France and in Europe, periurban forests are subject to high social demands for recreational purposes. These demands take the form of frequent visits for sports or rest. Local governments have succeeded in creating new wooded parks close to cities that are highly appreciated by the population. A survey was run on visitors to forests around three mid-sized cities, addressing what they do in the forests and why. The answers revealed differences between suburban parks and larger national forests located farther from the cities. New approaches targeting health may also be observed on the part of both individuals and the health sector. These new approaches indicate the existence of a wellness function in periurban forests.